Using Journey Mapping within Extension: A Tool for Supporting Behavior Change Programs - Colby Silvert; Laura A. Sanagorski Warner (EDIS)
Extension is an important change agency, and Extension professionals use innovative strategies to help target audiences to adopt research-based practices and technologies. Tools from commercial marketing can be applied to behavior-change campaigns, often through an underused approach known as social marketing. Journey maps can be developed with Extension clients to provide insight into their progression and decision-making from one place or state of being to another. A journey can be the steps a person takes when selecting plants for the landscape, the decision-making process used when identifying agricultural business strategies, or the steps a person takes when leaving a workshop and travelling to their home. This new 9-page publication of the UF/IFAS Department of Agricultural Education and Communication, written by Colby Silvert and Laura A. Sanagorski Warner, presents possible applications of journey mapping within an Extension context. http://edis.ifas.ufl.edu/wc333